Increase Security of Li-Fi Technology by Using RSA Algorithm to Encryption and Decryption Important Data - Mohammed M. Ahmed; Satea H. Alnajjar (Al-Iraqia Journal for Scientific Engineering Research)
Communication systems are constantly evolving to keep pace with the increasing number of users and their digital transactions, and the need to increase the capacity of communication networks has emerged. However, hacking and phishing operations have increased to obtain or modify users' private data. As a result, it has become necessary to enhance network security measures to protect systems and users from hacking attempts by employing encryption techniques to secure important data. In the proposed system, a communication system using advanced Li-Fi technology was developed and tested in different weather conditions and at different distances, and the system was protected using RSA technology to encrypt data and, transmit it over the network and then decrypt it at the receiving end. This approach has shown positive results with the use of large prime numbers with a high level of resistance to hacking and decryption, ensuring the secure flow of network data.